Results of the British Association of Urological Surgeons female stress urinary incontinence procedures outcomes audit 2014–2017. (19th October 2018) - Cashman, Sophia; Biers, Suzanne; Greenwell, Tamsin; Harding, Chris; Morley, Roland; Cooper, David; Fowler, Sarah; Thiruchelvam, Nikesh; ,
Abstract : Objectives: To analyse the results of the stress urinary incontinence (SUI) audit conducted by the British Association of Urological Surgeons (BAUS), and to present UK urologists' contemporary management of SUI. Patients and Methods: The BAUS audit tool is an online resource, to which all UK urologists performing procedures for SUI are invited to submit data. The data entries for procedures performed during 2014–2016 were collated and analysed. Results: Over the 3‐year period analysed, 2917 procedures were reported by 109 surgeons, with a median of 20 procedures reported per surgeon. A total of 2 366 procedures (81.1%) were recorded as a primary surgery, with 548 procedures (18.8%) performed for recurrent SUI. Within the time period analysed, changes were noted in the frequency of all procedures performed, with a trend towards a reduction in the use of synthetic mid‐urethral tapes, and a commensurate increase in the use of urethral bulking agents and autologous fascial slings. A total of 107 (3.9% of patients) peri‐operative complications were recorded, with no association identified with patient age, BMI or surgeon volume. Follow‐up data were available on 1832 patients (62.8%) at a median of 100 days postoperatively. Reduced pad use was reported in 1311 of patients (84.5%) with follow‐up data available and 86.3% reported a pad use of one or less per day. In all, 375 patients (85%) reported being satisfied or very satisfied with the outcome of their procedure at follow‐up, although data entry for this domain was poor. De novo overactive bladder (OAB) symptoms were reported by 15.2% of patients (263/1727), and this was the most commonly reported postoperative complication. For those reporting pre‐existing OAB prior to their SUI surgery, 28.7% (307/1069) of patients reported they got better after their procedure, whilst 61.9% (662/1069) of patients reported no change and 9.4% of patients (100/1 069) got worse. Conclusions: This review identified that, despite urological surgeons undertaking a relatively low volume of procedures per year, SUI surgery by UK urologists is associated with excellent short‐term surgeon‐ and patient‐reported outcomes and low numbers of low grade complications. Complications do not appear to be associated with surgeon volume, nor do they appear higher in those undergoing mesh surgery. Shortfalls in data collection have been identified, and a longer follow‐up period is required to comment adequately on long‐term complications, such as chronic pain and tape extrusion/erosion rates.